A New Method of Evaluating Tight Sandstone Reservoir Pore Structure from Conventional Logs. Issue 1 (1st December 2016) - Xiao, Liang; Chang-chun, Zou; Xie, Xiu-hong
Abstract : The identification and evaluation of tight gas sandstone reservoirs faces a great challenge due to the characteristics of ultra-low porosity, ultra-low permeability, complicated pore structure and strong heterogeneity. To improve tight gas sandstone reservoir evaluation, the pore structure should be first quantitatively evaluated. NMR logs are advantageous in formation pore structure evaluation, but may not always be practicable as they are only acquired in limited wells. This study is based on the analysis of morphological characteristics of experimental mercury injection capillary pressure (MICP) curves for 54 core samples from tight gas sandstone reservoirs of central Sichuan Basin, southwest China. A new method is proposed to construct pseudo capillary pressure curves from conventional porosity and permeability. The corresponding models of predicting pseudo Pc curves from conventional logs are established. The reliability of this technique is verified by comparing constructed capillary pressure curves with laboratory measured results. After this technique is extended to field application, consecutive pseudo capillary pressure curves are constructed, and the parameters associated with reservoir pore structure evaluation, such as pore throat radius distribution, the average pore throat radius, the threshold pressure, and so on, are estimated. Combining with these parameters, tight gas sandstone reservoirs pore structures are quantitatively evaluated, and effective formations can be easily identified. The proposed technique is more universally applicable in tight gas sandstone reservoir pore structure evaluation as it does not require the acquisition of field NMR logs.